A novel variant of the IFITM5 gene within the 5′‐UTR causes neonatal transverse clavicular fracture: Expanding the genetic spectrum. Issue 7 (8th May 2020) - Wu, Dong; Wang, Yuxin; Huang, Huijuan
Abstract: Background: Osteogenesis imperfecta (OI) type V is a rare heritable bone disorder caused by pathogenic variants of IFITM5 . Only two mutated alleles in IFITM5 have been identified worldwide, the role of which in OI pathology is not fully understood. Methods: A neonatal case of suspected OI, clinically manifested as a rare clavicle transection fracture with delayed early fracture healing, was studied. Subtle variants of OI‐associated genes were analyzed by whole exome sequencing and confirmed by Sanger sequencing. Results: A de novo heterozygous pathogenic variant of IFITM5 within the 5′‐UTR (c.‐9C > A) was discovered in the proband. Bioinformatics analysis using a combination of various algorithms predicted that the variant would generate a new in‐frame start codon 9 bp upstream of the original and express a mutant IFITM5 protein with three additional amino acids (Met‐Glu‐Pro). After transfection into a eukaryocyte in vitro, the mutant IFITM5 construct produced a longer transcription product than that of wild‐type IFITM5. Conclusion: This study identified a novel pathogenic variant of IFITM5, which not only manifested the molecular characteristics of IFITM5, but also provided new evidence for the study of the molecular mechanisms of IFITM5 association with OI. Abstract : A novel variant of the IFITM5 gene within the 5′‐UTR is identified. This study manifested the molecular characteristics of osteogenesis imperfecta. N‐terminal sequences are important to the function of IFITM5.